Library service management as an effort to cultivate students' reading interest in improving activities and learning outcomes - Hamdani Fajar Apriwulan; Akhmad Hanama; Siti Atwano Pisriwati; Deny Hadi Siswanto (Curricula: Journal of Curriculum Development, 2025)
The good condition of the school library supports students' interest in reading by providing supportive services for improving students' activities and learning outcomes. This study aims to analyze the planning of library services to increase reading interest and evaluate and assess the evaluation of library services in increasing students' reading interest in SMA Muhammadiyah Mlati as part of improving activities and learning outcomes. This study uses a qualitative descriptive approach with a case study method and data analysis techniques, including data collection, condensation, data presentation, and decision-making. The study results revealed that library service planning to increase students' interest in reading includes service-based programs and habituation supported by the procurement of collections, infrastructure, and budgets. In addition, there are also circulation services with an open service system and habit-based programs implemented through the "Sejali" program for a quarter of an hour of literacy. The evaluation of library services is carried out through monitoring and follow-up to improve the quality of library services and students' interest in reading to improve students' activities and learning outcomes.   Abstrak Kondisi perpustakaan sekolah yang baik menunjang minat baca siswa dengan menyediakan layanan yang mendukung untuk peningkatan aktivitas dan hasil belajar peserta didik. Tujuan dari penelitian ini untuk menganalisis perencanaan layanan perpustakaan yang bertujuan meningkatkan minat baca, mengevaluasi dan menilai evaluasi layanan perpustakaan dalam meningkatkan minat baca siswa di SMA Muhammadiyah Mlati sebagai bagian dari peningkatan aktivitas dan hasil belajar. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode studi kasus, serta teknik analisis data, meliputi proses pengumpulan data, kondensasi data, penyajian data, dan pengambilan keputusan. Hasil penelitian mengungkapkan bahwa perencanaan layanan perpustakaan yang bertujuan meningkatkan minat baca peserta didik mencakup program berbasis layanan dan pembiasaan yang didukung oleh pengadaan koleksi, sarana prasarana, dan anggaran. Selain itu, terdapat juga layanan sirkulasi dengan sistem layanan terbuka dan program berbasis pembiasaan yang dilaksanakan melalui program “Sejali” seperempat jam literasi. Evaluasi layanan perpustakaan dilakukan melalui monitoring dan tindak lanjut untuk meningkatkan kualitas layanan perpustakaan dan minat baca peserta didik untuk peningkatan aktivitas dan hasil belajar peserta didik. Kata Kunci: hasil belajar; layanan perpustakaan; manajemen perpustakaan; minat baca siswa